The Relationship between Sustainable Supply Chain Practices and Economic Value Added of the Company in the Light of Corona Pandemic - Tohamy, Khaled Sobeh El Hady; Zaitoun, Noha Mahmoud Ashraf Mohamed Ali (The Arab Journal of Administration, 2025)
This research paper aimed at investigating the relationship between sustainable supply chain practices (internal environmental management, environment-friendly design, sustainable purchasing, sustainable manufacturing, cooperation with clients, and reverse logistics) as the independent variables, and the economic value added of the company as the dependent variable. A study sample of thirty companies was chosen from various industrial sectors among the companies listed on the Egyptian stock exchange market. A total of 150 observations were obtained representing the time period 2016 – 2020. The financial statements of the companies were analyzed in order to discover the improvement or deterioration incurred by their economic value added due to the application of sustainable supply chain practices. In addition, in-depth analytical interviews were conducted with a number of department managers in the companies under study. The collected data were analyzed using descriptive measures, frequencies, the regression analysis and the correlation coefficient. After carrying out the necessary statistical tests, the study results revealed a positive effect of the sustainable supply chain practices on the economic value added at the company level.